Uterine myomas treated with microwave ablation: The agreement between ablation volumes obtained from contrast-enhanced sonography and enhanced MRI. (February 2014) - Lei, Feng; Jing, Zhang; Bo, Wen; Dongmei, Hu; Zhencai, Li; Xue, Jiang; Fang, Wang; Hongyu, Zhou; Jintao, Ren
Abstract Purpose: This study explores the agreement between ablated uterine myoma volumes obtained from contrast-enhanced sonography and enhanced magnetic resonance imaging (MRI) after microwave ablation therapy. Materials and methods: Twenty uterine myomas in 18 patients (average size: 5.56 ± 1.26 cm) were successfully treated by microwave ablation. Contrast-enhanced sonography and enhanced MRI were performed within 7 days after the treatment. The ablation range of uterine myomas was observed and the ablation volume was calculated. By using the intraclass correlation coefficient (ICC) and Bland-Altman regression analysis, the agreement between ablated uterine myoma volumes obtained from contrast-enhanced sonography and enhanced MRI after microwave ablation therapy was analysed. Results: The ablated volume ranged from 13.66 to 135.27 cm3 after ablation, and the mean volume was 66.59 ± 35.71 cm3 by using contrast-enhanced sonography. Respectively, the ablated volume ranged from 10.88 to 137.83 cm3, and the mean volume was 66.81 ± 35.45 cm3 by using enhanced MRI. The limits of agreement between the two methods were (−10.83 cm3, 8.39 cm3), ICC was 0.991 (F = 209.61, P < 0.05), and 95% confidence interval is (0.976, 0.996). The results revealed a good agreement between the two examination methods of contrast-enhanced sonography and enhanced MRI. Conclusions: Contrast-enhanced sonography and enhanced MRI can be used interchangeably in observing the ablation range of uterine myomas treated with microwave ablation. Contrast-enhanced sonography can be used as a preferred non-invasive examination and for follow-up. Meanwhile, enhanced MRI can be used to comprehensively determine the relationships among uterine myomas, the entire uterus, and surrounding tissues.